Bone marrow CD34+ molecular chimerism as an early predictor of relapse after allogeneic stem cell transplantation in patients with acute myeloid leukemia - Malagola, Michele; Polverelli, Nicola; Beghin, Alessandra; Bolda, Federica; Comini, Marta; Farina, Mirko; Morello, Enrico; Radici, Vera; Accorsi Buttini, Eugenia; Bernardi, Simona; Re, Federica; Leoni, Alessandro; et al. (Frontiers in Oncology, 2023)
Background: minimal residual disease (MRD) monitoring is an important tool to optimally address post-transplant management of acute myeloid leukemia (AML) patients. Methods: we retrospectively analyzed the impact of bone marrow CD34+ molecular chimerism and WT1 on the outcome of a consecutive series of 168 AML patients submitted to allogeneic stem cell transplantation. Results: the cumulative incidence of relapse (CIR) was significantly lower in patients with donor chimerism on CD34+ cells ≥ 97.5% and WT1 < 213 copies/ABL x 10^4 both at 1st month (p=0.008 and p<0.001) and at 3rd month (p<0.001 for both). By combining chimerism and WT1 at 3rd month, 13 patients with chimerism < 97.5% or WT1 > 213 showed intermediate prognosis. 12 of these patients fell in this category because of molecular chimerism < 97.5% at a time-point in which WT1 was < 213 Conclusions: our results confirm that lineage-specific molecular chimerism and WT1 after allo-SCT (1st and 3rd month) are useful MRD markers. When considered together at 3rd month, CD34+ molecular chimerism could represent an earlier predictor of relapse compared to WT1. Further studies are necessary to confirm this preliminary observation.